New data from a subanalysis of the TRICOLOR study: antihypertensive effectiveness of the triple single-pill combination of amlodipine/indapamide/perindopril and predictors of effectiveness and blood pressure control in young patients - Yu. A. Karpov; N. A. Logunova; B. B. Kvasnikov; Yu. V. Khomitskaya (Российский кардиологический журнал)
Aim. To describe the antihypertensive efficacy of triple fixeddose combination of amlodipine/indapamide/perindopril and assess the predictors of efficacy in young patients (<50 years).Material and methods. The TRICOLOR study (NCT03722524) is an observational prospective study (n=1247) that demonstrated high antihypertensive effectiveness and good tolerability of the triple singlepill combination (SPC) of amlodipine/ indapamide/perindopril. This subgroup analysis was performed on 199 patients aged <50 years (16% of the total population), and the comparison group consisted of 925 patients (82,3% of the total population) aged 50 years or older.Results. In young patients, during triple therapy with SPC amlodipine/indapa mide/perindopril, a positive trend in blood pressure (BP) reduction was observed compared to the baseline: an average decrease in BP after 12 weeks was 32,6 (11,0)/14,8 (8,5) mm Hg (p<0,0001), comparable to patients over 50 years of age in terms of reduction in systolic blood pressure (SBP) and diastolic blood pressure (DBP) after 2, 4 and 12 weeks of followup. A greater number of young patients achieved a reduction in blood pressure <140/90 mm Hg after 2 weeks of therapy compared to patients 50 years of age and older (49,7% vs 38,8%, p=0,004), and blood pressure <130/80 mm Hg – after 4 and 12 weeks (51,3% vs 43,5% (p=0,041) and 74,9% vs 67,5% (p=0,038), respectively). Left ventricular hypertrophy was a significant negative predictor of SBP reduction by 12 weeks of therapy, and the presence of grade 2 hypertension (HTN) and statin use, on the contrary, were positive predictors of changes in SBP by the end of observation. More adherent younger patients were significantly more likely to have a decrease in DBP by 12 weeks of follow-up. In addition, in young patients, male sex and the presence of dyslipidemia significantly increased the chances of blood pressure control at the end of observation. Waist circumference, body mass index, and grade 2 HTN were negative predictors of achieving the target blood pressure level.Conclusion. Thus, in young patients, good antihypertensive effectiveness of amlodipine/indapamide/perindopril was observed, comparable in the degree of blood pressure reduction with the older age group of 50 years and older.